Age at immigration and the intergenerational income mobility of the 1.5 generation - Marie Connolly; Catherine Haeck; Anne Mei Le Bourdais-Coffey (Université du Québec à Montréal, École des sciences de la gestion (ESG UQAM), Groupe de recherche sur le capital humain (GRCH), 2023)
In this paper, we exploit intergenerationally-linked tax files and Census data to first document the intergenerational income transmission between individuals who immigrated to Canada as children-the 1.5 generation-and their parents. We find that the correlation between parental income rank and child income rank becomes stronger the older the child is at arrival. We then try to get at the causal effect of the age at immigration by estimating a model in which child rank is explained by interactions between age at arrival and the average predicted rank of second-generation immigrants from the same region of origin, living in the same region in Canada, from the same birth cohort, given their parental income. The model gives us the rate at which children from the 1.5 generation catch up to second-generation immigrants. We find that up to age 10, the relation between age at immigration and income is flat, but starting at age 11, each year is associated with 3.3 fewer percentile ranks.
Keywords: J62; J61; J15; 330; intergenerational income mobility; immigrants; 1.5 generation; age at immigration; Canada